IMF Staff papers : Volume 30 No. 2. (IMF Staff Papers; IMF Staff Papers ;, 1983)
This paper presents the demonstration effect imparted by the economic performance of a select group of developing countries, particularly in Southeast Asia, where the growth of trade has played a major role. The outward-oriented strategies have been typically characterized, inter alia, by the provision of incentives for export production, the encouragement of import competition for most domestically produced goods, and the use of the nominal exchange rate for the maintenance of realistic real exchange rates. The generally increasing integration of the world economy, in both goods and capital markets, has meant that countries have been drawn into closer international relationships, whether expressly desired or not. The longer-term factors just discussed can clearly inhibit the opening up of an economy, but perhaps equally important in this context are the short-run and medium-run effects that occur when such a strategy is adopted. Simple casual observation shows that there are serious, even if transitory, costs as a country moves from a relatively closed economy to a more open one.